Contributions to the knowledge of Neotropical ant-like spiders: Myrmecotypus tahyinandu sp. n. from Bolivian Chiquitano forest, a new country record for M. niger, and indirect evidence for species-specific mimicry (Araneae: Corinnidae: Castianeirinae) - Perger, Robert; Rubio, Gonzalo D. (Zootaxa, 2020)
Myrmecotypus tahyinandu sp. n. is described from the Bolivian Chiquitano forest, and M. niger Chickering, 1937 is recorded from Bolivia for the first time. The morphological differentiation among the closely related M. tahyinandu sp. n. and M. iguazu Rubio & Arbino, 2009 is likely attributable to the selection for specific ant mimicry. Adults of M. tahyinandu sp. n. are accurate mimics of the ant Camponotus crassus Mayr, 1862, M. iguazu of C. sericeiventris (Guérin-Méneville, 1838), and M. niger of Dolichoderus bispinosus (Olivier, 1792). This study is the first to identify ant models for morphologically closely related Castianeirinae, providing a promising starting point for future research on ant mimicry.